Understanding the impact of oil shocks - Conraria, Luís Aguiar (2005)
This paper provides new empirical evidence on and theoretical support for the close link between oil prices and aggregate macroeconomic performence in the 1970s. Although this link has been well documented in the empirical literature and is further confirmed in this paper, standard economic models are not able to replicate this link when actual oil prices are used to stimulate the models. In particular, standard models cannot explain the depht of the recession in 1974-75 and the strong revival in 1976-78 based on the oil price movements in that period. This paper argues that a missing multiplier-accelerator mechanism from standard models may hold the key. This multipliplier-accelerator mechanism not only exacerbated the impact of the oil schocks in 1973-74 but also helped create the temporary recovery in 1976-1978. This paper derives the missing multiplier-accelarator mechanism from externalities in general equilibrium. Our calibrated model can explain both the recession in 1974-75 and revival in 1976-78.